A dynamic approach for modelling and simulation of motor unit discharge behaviour using recurrent fuzzy-techniques - Heller, M.; Witte, K. (International Journal of Computer Science in Sport, 2006)
A dynamic approach for modelling and simulation of motor unit discharge behaviour using recurrent fuzzy-techniques is presented. The model is able to generate a nominal force-time curve by means of the discharge behaviour of a single motor unit pool using the knowledge of various seemingly isolated findings that have been reported. In several simulations, it has been shown that recurrent fuzzy systems are able to approximate dynamic behaviour in terms of nominal/actual force value regulation. First results suggest that there might be optimal motor unit co-ordination patterns relating to a given task: in first MVC-simulations variation of about 10% has been shown. In spite of the difficulties to verify the model experimental examination is necessary to confirm the results. This kind of research is fundamental to understand mechanisms that yield to increased muscle performances in sports.